2016
DOI: 10.2147/ppa.s108688
|View full text |Cite
|
Sign up to set email alerts
|

Sexual attitudes, norms, condom use, and adherence of Hispanic and non-Hispanic undergraduate students: a cross-sectional study of three community colleges in southwestern US

Abstract: ObjectiveTo measure the sexual attitudes, norms, condom use, and adherence of Hispanic and non-Hispanic undergraduate students in three community colleges in the southwestern US.MethodsA previously validated instrument was used in this study (sexual risk behavior beliefs and self-efficacy survey). Statistical analyses included chi-square and one-way analysis of variance with post hoc multiple comparisons using the Statistical Program for the Social Sciences.ResultsThe study participants included 234 first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The Latinx cultural value of marianismo prescribes traditional gender role beliefs and subordinance in sexual decision-making (Castillo et al, 2010). Unprotected sex contributes to higher rates of unwanted pregnancies and STIs among Latina college students compared to White college student women (Bird et al, 2016).…”
Section: Sexual Health Disparities Among Latina Young Adult College S...mentioning
confidence: 99%
“…The Latinx cultural value of marianismo prescribes traditional gender role beliefs and subordinance in sexual decision-making (Castillo et al, 2010). Unprotected sex contributes to higher rates of unwanted pregnancies and STIs among Latina college students compared to White college student women (Bird et al, 2016).…”
Section: Sexual Health Disparities Among Latina Young Adult College S...mentioning
confidence: 99%
“…Perceived social norms supporting sexual behavior with NRP and FSW may be a facilitator for male factory workers to regulate and intimate. Prior studies showed that perceived social norms had considerably facilitated risky sexual behavior among colleges and adolescents in the United States [ 37 , 38 , 39 ]. Furthermore, perceived social support is potentially important as a protective factor of psychological health promotion [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Greater knowledge of the risks of unprotected sex is associated with a greater likelihood of condom use, but previous studies suggest that health knowledge is necessary but not sufficient to lead to behavioural change [ 18 , 22 ]. This may be explained by the distinction between cognitive responses—the thoughts or beliefs surrounding a subject—and affective responses—the emotions evoked by the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the one-time stigma related to condom use has shifted. In pre-2000 studies in the West, shame, guilt and embarrassment associated with condom use was partially attributed to the stigma related to homosexuality [ 18 ] whereas more recent studies suggest shame, guilt and embarrassment associated with condom use centre on the perception that their use implies a lack of trust in a partner [ 22 , 24 ]. We are particularly interested in this and other psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%